PARADIGMA DALAM ANTROPOLOGI: ANALISIS TERHADAP KARYA ANDREW BEATTY, VARIETIES OF JAVANESE RELIGION: AN ANTHROPOLOGICAL ACCOUNT - Isfironi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
Anthropology is one of the social-humanity sciences that deals with culture. The existence of the division of science is divided into two categories, name-ly Natuurwissenschaften and Geisteswissenschaften which shows that the reality of the natural sciences has a different character from the social sci-ences-humanity. To understand an anthropological work well, the work needs to be weighed within the framework of the paradigm. With this scales a work will be more clearly identified from the basic assumptions to the the-ory that the conclusion of the study. With the paradigm framework, Andrew Beatty's Varieties of Javanese Religion: An Anthropological Account can be summed up in the tradition of the Hermeneutic epistemology. Hermeneutics is in charge of interpreting the expressions of human inner life, whether in the form of gestures, historical actions, codified law, works of art or litera-ture. From the epistemology of Hermeneutik is born two paradigms which one of them is a cultural interpretation. With the cultural interpretation it al-lows Beatty to uncover the meaning of any cultural phenomenon captured in the everyday life of Bayu society.